1997
DOI: 10.1002/(sici)1520-6300(1997)9:3<291::aid-ajhb2>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships of age and the body mass index with risk factors of non-insulin dependent diabetes in European and migrant Asian males

Abstract: A comparative study of the interrelationships of age and the body mass index (BMI) with several risk factors for non‐insulin‐dependent diabetes mellitus (NIDDM) in adult White European (hereafter called European n = 262) and migrant Indian (n = 39) and Pakistani (n = 100) males residing in Peterborough, East Anglia, revealed significantly lower mean total cholesterol (TC), but higher mean diastolic blood pressure (DBP) in Asian men. Similar associations between age and fasting blood glucose (FBG), total choles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Results of the present study indicated that there existed no significant relationship of BMI with any of the metabolic risk factors for CHD. Similar results were obtained in a recent study among migrant Indians in Britain (Bose and Mascie-Taylor, 1997) which also reported that BMI did not have significant association with metabolic risk factors of CHD. These results suggest that among Indians, both migrant as well as native, BMI does not have strong association with metabolic risk factors of CHD.…”
Section: Discussionmentioning
confidence: 99%
“…Results of the present study indicated that there existed no significant relationship of BMI with any of the metabolic risk factors for CHD. Similar results were obtained in a recent study among migrant Indians in Britain (Bose and Mascie-Taylor, 1997) which also reported that BMI did not have significant association with metabolic risk factors of CHD. These results suggest that among Indians, both migrant as well as native, BMI does not have strong association with metabolic risk factors of CHD.…”
Section: Discussionmentioning
confidence: 99%
“…Body mass index (BMI) is the most commonly used indirect measure of overall adiposity (Bose and Mascie-Taylor, 1997;Bhadra et al, 2001;Ghosh et al, 2001Ghosh et al, , 2003Ghosh et al, , 2004Bose and Mukhopadhyay, 2004), while percent body fat (PBF), fat mass (FM), fat free mass (FFM), and fat mass index (FMI) are the most widely studied measures of body composition (VanItalie et al, 1990;Wang and Bachrach, 1996;Bose, 1998;Mueller et al, 2003). Prediction of PBF from skinfold thicknesses is an acceptable method for the assessment of body composition in children and adolescents (Deurenberg et al, 1990;Williams et al, 1992;Mueller et al, 2003).…”
Section: Introductionmentioning
confidence: 99%